Antitoxin MqsA Represses Curli Formation Through the Master Biofilm Regulator CsgD - Soo, Valerie W. C. (Sci Rep, 2013)
MqsA, the antitoxin of the MqsR/MqsA toxin/antitoxin (TA) system, is a global regulator that reduces expression of several stress response genes (e.g., mqsRA, cspD, and rpoS) by binding to the promoter palindromic motif [5′-AACCT (N)(3) AGGTT-3′]. We identified a similar mqsRA-like palindrome [5′-AACCT TA AGGTT-3′] 78 bp upstream of the transcription initiation site in the csgD promoter (p-csgD). CsgD is a master regulator for biofilm formation via its control of curli and cellulose production. We show here that MqsA binds to this palindrome in p-csgD to repress csgD transcription. As expected, p-csgD repression by MqsA resulted in reduced transcription from CsgD-regulated curli genes csgA and csgB (encoding the major and minor curlin subunits, respectively). Curli production was reduced in colonies and in planktonic cells upon MqsA production. Hence, MqsA directly represses p-csgD, and thereby influences curli formation. This demonstrates that TA systems can impact overall cell physiology by fine-tuning cellular stress responses.